Resuscitation Education Science: Educational Strategies to Improve Outcomes From Cardiac Arrest. Issue 6 (7th August 2018) - Cheng, Adam; Nadkarni, Vinay M.; Mancini, Mary Beth; Hunt, Elizabeth A.; Sinz, Elizabeth H.; Merchant, Raina M.; Donoghue, Aaron; Duff, Jonathan P.; Eppich, Walter; Auerbach, Marc; Bigham, Blair L.; Blewer, Audrey L.; et al.
Abstract : The formula for survival in resuscitation describes educational efficiency and local implementation as key determinants in survival after cardiac arrest. Current educational offerings in the form of standardized online and face-to-face courses are falling short, with providers demonstrating a decay of skills over time. This translates to suboptimal clinical care and poor survival outcomes from cardiac arrest. In many institutions, guidelines taught in courses are not thoughtfully implemented in the clinical environment. A current synthesis of the evidence supporting best educational and knowledge translation strategies in resuscitation is lacking. In this American Heart Association scientific statement, we provide a review of the literature describing key elements of educational efficiency and local implementation, including mastery learning and deliberate practice, spaced practice, contextual learning, feedback and debriefing, assessment, innovative educational strategies, faculty development, and knowledge translation and implementation. For each topic, we provide suggestions for improving provider performance that may ultimately optimize patient outcomes from cardiac arrest.